If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -3(y + -4) + 2 = 7 Reorder the terms: 4y + -3(-4 + y) + 2 = 7 4y + (-4 * -3 + y * -3) + 2 = 7 4y + (12 + -3y) + 2 = 7 Reorder the terms: 12 + 2 + 4y + -3y = 7 Combine like terms: 12 + 2 = 14 14 + 4y + -3y = 7 Combine like terms: 4y + -3y = 1y 14 + 1y = 7 Solving 14 + 1y = 7 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 1y = 7 + -14 Combine like terms: 14 + -14 = 0 0 + 1y = 7 + -14 1y = 7 + -14 Combine like terms: 7 + -14 = -7 1y = -7 Divide each side by '1'. y = -7 Simplifying y = -7
| y=-1/2*-0.05+4 | | y=-1/2*4+4 | | y=-0.05*4+4 | | 5y+2=3(y+4) | | y=-0.05*-0.05+4 | | 1/2+3/4-1/3= | | y=-0.5*-0.5+4 | | y=0.4*2+2 | | 5q-3n/m=f | | y=0.4*0.4+2 | | 4x-6=66 | | 7x+2x=12 | | 7(x-3)=39 | | 3/4s+1/5s=4/5 | | 8*8+4y=32 | | 2(x-9)=11 | | 63000=10x-2000 | | y=10x^2-15x+3 | | 4x^2-5x=10 | | 8-4x=12-3x | | P(x)=10x-2000 | | 10r-21=33 | | 123*65/2 | | 10*10-6y=-60 | | -1(9+1)+1= | | (24-y)/4=4 | | 10x-6*10=-60 | | x^2+8y-16=0 | | 10*6-6y=-60 | | 7/8x+5-3/8x-4 | | 17y-22y=0 | | 1/2a-5-1/2a |